Modification of a disordered Ni3Fe alloy surface by 50 keV Zr ion implantation; Thin Solid Films; Vol. 308-309, № 1-4 (31 October 1997) - Sharkeev Y. P.; Perry A. J.; Geist D. E.; Ryabchikov A. I. Aleksandr Ilyich; Tailashev A. S.; Girsova N. V.; Kozlov E. V. (1997, 1997)
It is well known that after ion implantation, microstructural changes are found at depths well beyond the range of the implanted ions. In the present work samples of a disordered Ni3Fe alloy, implanted with four doses of a multicomponent ion beam (where the principal component was zirconium) in the range 0.6-6.0 × 1017 ions cm-2, have been studied by transmission electron microscopy with subsidiary measurements being made of microhardness and residual stress in some of the samples. It is found that the implanted zone becomes increasingly amorphous and ZrO2 precipitates of increasing size appear as the implanted dose increases. These are accompanied by high internal stresses evidenced by electron micro-diffraction and confirmed by X-ray diffraction measurements. Immediately below the implanted zone, the dislocation density is increased by 2-3 times, depending on the implanted dose, and decreases monotonically down to a depth of about 10 μm. This is accompanied by corresponding increases in microhardness and residual stress which becomes increasingly tensile with the implanted dose.